The Ability Gradient in Bunching - Spencer Bastani; Daniel Waldenström (Research Institute of Industrial Economics (IFN), 2020)
We analyze the relationship between cognitive ability and bunching in the context of a large and salient kink point of the Swedish income tax schedule. Using population-wide register data from the Swedish military enlistment and administrative tax records, we find that high-ability individuals bunch more than low-ability individuals. This ability gradient is stronger for the self-employed, but is also present among wage earners. We also use high-school GPA and math grades to analyze gender differences, finding a stronger ability gradient among men.
Keywords: H21; H24; J22; J24; 330; Bunching; Ability; Skills; Complexity; Optimal Taxation